Isu-isu pluralisme agama dalam Tuntutan Comango: satu analisis terhadap laporan 2013 dan 2018 - Earnie Elmie Hilmi,; Kamarudin Salleh,; Nur Farhana Abd Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Coalition of Malaysian NGO’s in the UPR Process (COMANGO) is a group combines several non-governmental organizations (NGOs) in Malaysia. COMANGO has submitted a human rights report to the UN Human Rights Council's Universal Periodic Review process under the UN in 2013 in Geneva. They submitted several requests to the Malaysian government to agree and sign it. There are 17 issues raised, but there are some demands that became controversial including freedom of religion in relation to the right of apostasy and the right of teaching other than Ahl Sunnah wal Jamaah such as Shi'ah, Qadiani, Ahmadiah and others; the privileged position of the Malays; the right of lesbian, gay, bisexual, transgender, inter-sexed and queer persons (LGBTIQ); as well as intervention attempts in the affairs of the Syariah Court. This research uses qualitative method of document analysis on the COMANGO report of 2013 and 2018 in order to analyse its demands and its relevance to issues of religious pluralism. From this analysis, COMANGO's demandss related to issues of religious pluralism amongst others are the apostasy issue, the word Allah and the issue of Article 121 (1A).